Level of Knowledge as a Dominant Factor in Pregnant Women's Visits: a Mixed Methods Study - Iradatul Aini; Firdawati Firdawati; Husna Yetti (Journal La Medihealtico, 2025)
The Maternal Mortality Rate (MMR) in Padang City has increased during the 2018-2020 period. One of the efforts to reduce MMR is to provide integrated pregnancy services. The coverage of K1, K4, and K6 pregnancy visits is an important indicator in assessing the quality of these services, but the achievements of the three in 2019-2022 in Padang City have not reached the target. This study aims to find out the factors related to the visit of pregnant women to the Health Center. The method used is a mixed method with a cross sectional and sequential explanatory design. A total of 142 pregnant women in the third trimester became respondents in quantitative research, and 11 informants in qualitative research. The research was conducted in three health centers in Padang City. The results of the quantitative analysis showed that of the 10 variables studied, the level of knowledge had a significant relationship with pregnant women's visits (p = 0.009), and was the most dominant factor based on multivariate tests. The qualitative results showed that most of the respondents obtained information from digital platforms, but the Mother And Child Health book has not been used to the fullest, the classes of pregnant women are not evenly distributed, and there is still an assumption that pregnancy is a natural process that does not need to be studied. Efforts are needed to improve health promotion and education for pregnant women to increase knowledge and awareness about the importance of pregnancy visits, so that the target of pregnancy service coverage can be achieved.